Session Chair - Christofi, Michael (My University, 2026)
The purpose of the International Marketing Review (3* ABS) Special Issue (SI) Paper Development Workshop (PDW) was to introduce the journal, as well as the specific SI, to interested conference participants. In particular, the PDW seeks to introduce the systematic literature review methodology to both junior and senior scholars and provide them with developmental feedback on their current systematic literature review papers in International Marketing research.